Electrolyte for electrolytic copper foil, method for preparing copper foil and copper foil
By using improved electrolyte formulation and foil-grinding machine grinding technology in the production of electrolytic copper foil, the problems of large amount of additives and difficult control in the existing processes have been solved, and the elongation of copper foil has been significantly improved.
Patent Information
- Application Number
- CN202411749922.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing high-performance copper foil production process, there are many additive components, large amounts of usage and difficult control, which leads to difficult control of the production process.
An electrolytic solution for electrolytic copper foil is provided, including copper ions, sulfate ions, chloride ions, collagen peptides, polyethylene glycol, hydroxyethyl cellulose, sodium polydithiodipropane sulfonate, and 0.25-0.55 mg/L of sodium N,N-dimethyldithioformamide propane sulfonate, and copper foil is prepared by electrolytic treatment of the foil.
By improving the electrolyte formulation and the grinding accuracy of the foil germination machine, the elongation of the copper foil can be significantly improved, with an elongation of up to 18%, and the roughness of the cathode roller is improved.
Smart Images

Figure CN119710840A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolytic copper foil preparation, in particular to an electrolyte for electrolytic copper foil, a method for preparing the copper foil, and the copper foil. Background Art
[0002] High elongation means that the copper foil has good winding resistance and flexibility, and is an important indicator of the process level of lithium battery copper foil. Since lithium batteries are repeatedly charged and discharged during use, the battery cells shrink and expand repeatedly. High elongation copper foil can effectively reduce the possibility of breakage during the shrinkage and expansion process, thereby improving the safety of lithium batteries during use.
[0003] The existing technical solutions have the following disadvantages: the additive components in the production of high-performance copper foil are numerous, the dosage is large, the effects are complex, and the control and use of the content of each component are unclear, making the production process control very difficult. Summary of the invention
[0004] The main technical problem solved by the present application is to provide an electrolyte for electrolytic copper foil and a method for preparing copper foil and copper foil, so as to improve the elongation of lithium battery copper foil.
[0005] To solve the above problems, the first aspect of the present application provides an electrolyte for electrolytic copper foil, wherein the electrolyte for electrolytic copper foil comprises: copper ions, sulfate ions, chloride ions, collagen peptides, polyethylene glycol, hydroxyethyl cellulose, sodium polydisulfide propane sulfonate, and 0.25-0.55 mg / L of sodium N,N-dimethyldithiocarboxamide propane sulfonate.
[0006] In a specific embodiment, the combined solvent additive includes collagen peptides with a molecular weight of 1500-4000, polyethylene glycol with a molecular weight of 6000, hydroxyethyl cellulose, and sodium polydisulfide dipropane sulfonate.
[0007] In a specific embodiment, in the electrolyte for electrolytic copper foil, the concentration of the collagen peptide is 12-20 mg / L, the concentration of the polyethylene glycol is 1-3 mg / L, the concentration of the hydroxyethyl cellulose is 0.1-0.18 mg / L, and the concentration of the sodium polydisulfide propane sulfonate is 6-10 mg / L.
[0008] In a specific embodiment, the molecular weight of the collagen peptide is 1500-6000, and the molecular weight of the polyethylene glycol is 4000-6000.
[0009] In a specific embodiment, the electrolyte for electrolytic copper foil includes copper ions at a concentration of 80-95 g / L and sulfate ions at a concentration of 90-100 g / L.
[0010] In a specific embodiment, the concentration of the chloride ions is 15-30 ppm.
[0011] In order to solve the above problems, the second aspect of the present application provides a method for preparing copper foil using the electrolytic copper foil electrolyte described in any embodiment of the first aspect, wherein the electrolytic copper foil electrolyte is injected into an electrolytic cell; the electrolytic copper foil electrolyte is electrolytically treated by a foil raw machine to obtain copper foil; wherein the anode of the foil raw machine is a titanium coating, the cathode is a seamless drum-type titanium roller, and the current density of the electrolytic treatment is 50-65A / dm 2 .
[0012] In a specific embodiment, the roughness of the roller surface of the seamless drum-type titanium roller is no more than 0.25 μm.
[0013] In a specific embodiment, the step of electrolyzing the electrolytic copper foil with an electrolyte using a foil machine to obtain the copper foil includes: offline grinding the seamless drum-type titanium roller using a 400-800 mesh grinding wheel.
[0014] In a specific embodiment, after the step of offline grinding the seamless drum-type titanium roller using a 400-mesh grinding wheel to 800-mesh grinding wheel, it also includes: online grinding the seamless drum-type titanium roller using a 1000-mesh non-woven brush wheel to 1200-mesh grinding wheel.
[0015] To solve the above problems, the third aspect of the present application provides a copper foil, wherein the copper foil is prepared by the method for preparing copper foil using an electrolyte for electrolytic copper foil as described in any embodiment of the second aspect above.
[0016] The beneficial effect of the present application is that by adding collagen peptides, polyethylene glycol, hydroxyethyl cellulose, sodium polydisulfide propane sulfonate and 0.25-0.55 mg / L of sodium N,N-dimethyldithiocarboxamide propane sulfonate to the copper sulfate electrolyte, the elongation of the copper foil can be greatly improved, and further improving the roughness of the cathode roller of the foil machine can also improve the elongation of the copper foil, which can make the elongation of the copper foil as high as 18%. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 This is a schematic flow chart of an embodiment of a method for preparing copper foil using an electrolyte for electrolytic copper foil in the present application. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms of "a", "said", and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless otherwise clearly indicated above, and "multiple" generally includes at least two, but does not exclude the inclusion of at least one.
[0021] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the objects associated with each other are in an "or" relationship. The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence.
[0022] It should be understood that the terms "include", "comprises" or any other variations used herein are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, the elements defined by the sentence "includes..." do not exclude the presence of other identical elements in the process, method, article or device that includes the elements.
[0023] It should be noted that if the embodiments of the present application involve directional indications (such as up, down, left, right, front, back...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0024] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The presence of the phrase at each location in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0025] The present application provides an electrolyte for electrolytic copper foil, which includes copper ions, sulfate ions, chloride ions, collagen peptides, polyethylene glycol, hydroxyethyl cellulose, sodium polydisulfide propane sulfate and 0.25-0.55 mg / L sodium N,N-dimethyldithiocarboxamide propane sulfonate.
[0026] Among them, sodium N,N-dimethyldithiocarboxamide propane sulfonate can improve the brightness and ductility of copper foil.
[0027] In this embodiment, chloride ions, collagen peptides, polyethylene glycol, hydroxyethyl cellulose, sodium polydisulfide propane sulfate, and sodium N,N-dimethyldithiocarboxamide propane sulfonate are all additives. In this embodiment, based on copper sulfate electrolyte, chloride ion additives, collagen peptide additives, polyethylene glycol additives, hydroxyethyl cellulose additives, sodium polydisulfide propane sulfate additives, and sodium N,N-dimethyldithiocarboxamide propane sulfonate additives are added to the copper sulfate electrolyte.
[0028] Preferably, the concentration of collagen peptide is 12-20 mg / L, which has the effect of leveling grains and reducing roughness. The concentration of polyethylene glycol is 1-3 mg / L, which has a wetting effect. The concentration of hydroxyethyl cellulose is 0.1-0.18 mg / L, which is used to promote the growth of grains and inhibit pinholes. The concentration of sodium polydisulfide propane sulfonate is 6-10 mg / L, which plays a role in grain refinement and high-area scorching prevention in the copper plating process. The concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 0.25-0.55 mg / L, which is used to obtain a coating with good brightness and ductility.
[0029] Preferably, the collagen peptide is selected from collagen peptides with a molecular weight of 1500-6000, and the polyethylene glycol is selected from polyethylene glycol with a molecular weight of 5000-6000.
[0030] Preferably, in the electrolyte for electrolytic copper foil, the concentration of copper ions is 80-95 g / L, and the concentration of sulfate ions is 90-100 g / L.
[0031] Preferably, in the electrolyte for electrolytic copper foil, the concentration of chloride ions is 15-30 ppm.
[0032] The beneficial effect of this embodiment is that by adding collagen peptides, polyethylene glycol, hydroxyethyl cellulose, sodium polydisulfide propane sulfonate and 0.25-0.55 mg / L of sodium N,N-dimethyldithiocarboxamide propane sulfonate to the copper sulfate electrolyte, the elongation of the copper foil can be greatly improved.
[0033] The present application also provides a method for preparing an electrolyte for electrolytic copper foil, and the specific steps are as follows:
[0034] Step 1, adding metallic copper into a copper dissolving tank, then adding sulfuric acid and deionized water, and blowing in high-temperature air at 55-80° C. (specifically 70° C.) to prepare a copper sulfate solution.
[0035] Step 2, filtering the copper sulfate solution and cooling it to 50-54° C. through a heat exchanger.
[0036] Step 3, adding chloride ions, collagen peptides, polyethylene glycol, hydroxyethyl cellulose, sodium polydisulfide propane sulfonate, sodium N,N-dimethyldithiocarboxamide propane sulfonate and other additives to the copper sulfate solution.
[0037] The chloride ion additive may be sodium chloride, hydrochloric acid or other chloride ion-containing solvents.
[0038] Among them, the concentration of chloride ions is 15-30ppm, the concentration of collagen peptides is 12-20mg / L, the concentration of polyethylene glycol is 1-3mg / L, the concentration of hydroxyethyl cellulose is 0.1-0.18mg / L, the concentration of sodium polydisulfide propane sulfonate is 6-10mg / L, and the concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 0.25-0.55mg / L.
[0039] The present application also provides a method for preparing copper foil using an electrolytic copper foil electrolyte, that is, the application of the electrolytic copper foil electrolyte. Figure 1 , Figure 1 This is a schematic diagram of a process of preparing copper foil using an electrolytic copper foil electrolyte according to an embodiment of the present invention. Figure 1 As shown, the method includes:
[0040] Step S11: injecting electrolyte for electrolytic copper foil into the electrolytic cell.
[0041] Among them, the electrolyte for electrolytic copper foil includes 80-95g / L copper ions, 90-100g / L sulfate ions, 15-30ppm chloride ions, 12-20mg / L collagen peptides, 1-3mg / L polyethylene glycol, 0.1-0.18mg / L hydroxyethyl cellulose, 6-10mg / L sodium polydisulfide propane sulfonate, and 0.25-0.55mg / L sodium N,N-dimethyldithiocarboxamide propane sulfonate.
[0042] Step S12: using a foil machine to electrolyze the electrolytic copper foil with an electrolyte to obtain copper foil.
[0043] The anode of the foil machine is a titanium coating and the cathode is a seamless drum titanium roller. The current density during the electrolytic treatment is 50-65A / dm 2 .
[0044] Preferably, the roughness of the roller surface of the seamless drum-type titanium roller is not greater than 0.25 μm.
[0045] Preferably, the seamless drum-type titanium roller is ground offline using a 400-800 mesh grinding wheel, so that the roughness of the roller surface of the seamless drum-type titanium roller is not greater than 0.25 μm. Wherein, the offline grinding means that the cathode is disassembled and the cathode is polished using a 400-800 mesh PVA grinding wheel.
[0046] Furthermore, after offline grinding the seamless drum-type titanium roller using a 400-800 mesh grinding wheel, the method further includes: online grinding the seamless drum-type titanium roller using a 1000-1200 mesh non-woven brush wheel. The online grinding is performed directly on the raw foil machine without disassembly.
[0047] When the foil machine is not used for a long time, the seamless drum titanium roller is first ground offline using a 400-800 mesh PVA grinding wheel to grind the roller surface roughness of the seamless drum titanium roller to no more than 0.25 μm.
[0048] Over a certain period of time, whether in use or placed, the roller surface of the seamless titanium roller may be oxidized, resulting in an increase in its roughness. At this time, a 1000-1200 mesh non-woven brush wheel can be used to grind the seamless titanium roller online to keep the roller surface roughness at no more than 0.25μm, thereby ensuring that before the seamless titanium roller is used to electrolyze the electrolytic copper foil with the electrolyte, the roller surface roughness is maintained at no more than 0.25μm.
[0049] The beneficial effect of this embodiment is that the copper foil obtained by electrolyzing the polished cathode roller surface with a copper sulfate electrolyte added with collagen peptide, polyethylene glycol, hydroxyethyl cellulose, sodium polydisulfide propane sulfonate, and sodium N,N-dimethyldithiocarboxamide propane sulfonate has a good elongation. By improving the cathode roller surface and improving the electrolyte formula, the elongation of lithium battery copper foil can be improved.
[0050] The present application also provides a copper foil, wherein the copper foil is prepared from the electrolyte for electrolytic copper foil in the above embodiment or is prepared using the method for preparing copper foil using the electrolyte for electrolytic copper foil in the above embodiment.
[0051] In this embodiment, after the step of electrolyzing the electrolytic copper foil with an electrolyte using a foil machine to obtain the copper foil, the step further includes performing an anti-oxidation treatment on the copper foil using a chromium-containing anti-oxidation electroplating solution.
[0052] The copper foil produced by the above method has good elongation.
[0053] The present invention will be described in detail below through examples.
[0054] Comparative Example 1
[0055] The electrolyte for electrolytic copper foil includes copper sulfate electrolyte (copper ion concentration is 80-95 g / L, sulfate ion concentration is 90-100 g / L), and chloride ion concentration is 20 ppm.
[0056] The additive composition includes:
[0057] The concentration of collagen peptide (molecular weight 2000) was 20 mg / L;
[0058] The concentration of hydroxyethyl cellulose is 0.13 mg / L;
[0059] The concentration of polyethylene glycol (molecular weight 6000) was 1.5 mg / L;
[0060] Sodium polydisulfide dipropane sulfonate 6mg / L.
[0061] First, a 400-mesh grinding wheel is used for offline grinding, and then a 1000-mesh grinding brush roller is used for online polishing. During the electrolytic treatment, the current density is 60A / dm 2 . Anti-oxidation electroplating uses chromium-containing anti-oxidation liquid.
[0062] Example 1
[0063] The electrolyte for electrolytic copper foil includes copper sulfate electrolyte (copper ion concentration is 80-95 g / L, sulfate ion concentration is 90-100 g / L), and chloride ion concentration is 20 ppm.
[0064] The additive composition includes:
[0065] The concentration of collagen peptide (molecular weight 2000) was 12 mg / L;
[0066] The concentration of hydroxyethyl cellulose is 0.18 mg / L;
[0067] The concentration of polyethylene glycol (molecular weight 6000) was 2.5 mg / L;
[0068] Sodium polydisulfide dipropane sulfonate 8mg / L;
[0069] The concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 0.25 mg / L.
[0070] First, a 400-mesh grinding wheel is used for offline grinding, and then a 1000-mesh grinding brush roller is used for online polishing. During the electrolytic treatment, the current density is 55A / dm 2 . Anti-oxidation electroplating uses chromium-containing anti-oxidation liquid.
[0071] Example 2
[0072] The electrolyte for electrolytic copper foil includes copper sulfate electrolyte (copper ion concentration is 80-95 g / L, sulfate ion concentration is 90-100 g / L), and chloride ion concentration is 20 ppm.
[0073] The additive composition includes:
[0074] The concentration of collagen peptide (molecular weight 2000) was 12 mg / L;
[0075] The concentration of hydroxyethyl cellulose is 0.18 mg / L;
[0076] The concentration of polyethylene glycol (molecular weight 6000) was 2.5 mg / L;
[0077] Sodium polydisulfide dipropane sulfonate 8mg / L;
[0078] The concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 0.25 mg / L.
[0079] First, a 600-mesh grinding wheel is used for offline grinding, and then a 1200-mesh grinding brush roller is used for online polishing. The current density during the electrolytic treatment is 55A / dm 2 . Anti-oxidation electroplating uses chromium-containing anti-oxidation liquid.
[0080] Example 3
[0081] The electrolyte for electrolytic copper foil includes copper sulfate electrolyte (copper ion concentration is 80-95 g / L, sulfate ion concentration is 90-100 g / L), and chloride ion concentration is 20 ppm.
[0082] Additive components include:
[0083] The concentration of collagen peptide (molecular weight 2000) was 12 mg / L;
[0084] The concentration of hydroxyethyl cellulose is 0.18 mg / L;
[0085] The concentration of polyethylene glycol (molecular weight 6000) was 2.5 mg / L;
[0086] Sodium polydisulfide dipropane sulfonate 10 mg / L;
[0087] The concentration of sodium N,N-dimethyldithiocarboxamide propane sulfonate is 0.35 mg / L.
[0088] Use 400 mesh and 600 mesh grinding wheels for one round each, and then use 1200 mesh grinding brush roller for online polishing. The current density during the electrolytic treatment is 55A / dm 2 . Anti-oxidation electroplating uses chromium-containing anti-oxidation liquid.
[0089] The copper foils obtained by processing in Examples 1-3 and Comparative Example 1 were subjected to performance tests, and the test data are shown in the following table:
[0090] performance Comparative Example 1 Example 1 Example 2 Example 3 <![CDATA[Grammage g / m 2 > 72.5 73.1 72.8 73 Tensile strength(mpa) 342.1 345.2 352.0 347.3 Elongation(%) 10.31 15.01 16.39 18.19 Surface roughness (μm) 0.27 0.21 0.20 0.19 Roughness of matte surface (μm) 1.68 1.40 1.38 1.34 Warpage(mm) 3 2 3 3 Antioxidation (140℃, 15min) qualified qualified qualified qualified
[0091] As can be seen from the above table, the electrolyte for electrolytic copper foil in Examples 1-3 to which 0.25-0.55 mg / L of sodium N,N-dimethyldithioformamide propane sulfonate is added can significantly improve the elongation of the generated copper foil by 5%-8% compared with the electrolyte for electrolytic copper foil in Comparative Example 1 to which no sodium N,N-dimethyldithioformamide propane sulfonate is added.
[0092] The difference between Example 2 and Example 1 is that the grinding precision of the cathode roller is different. From the comparison between Example 2 and Example 1, it can be seen that increasing the grinding precision of the cathode roller, that is, the lower the roughness, the better the ductility of the generated copper foil.
[0093] The difference between Example 3 and Example 1 is that the concentration of sodium polydisulfide propane sulfonate in the additive and the grinding accuracy of the cathode roller are improved at the same time, so that the elongation of the copper foil can be as high as 18%. In Example 3, when the electrolysis temperature is controlled at 50-54°C and the current density is 50-55A / dm 2 , chloride ion concentration 20ppm, additive composition and concentration: collagen peptide (molecular weight 2000) concentration 12mg / L, hydroxyethyl cellulose concentration 0.18mg / L, polyethylene glycol (6000) 2.5mg / L, polydisulfide dipropane sulfonate sodium 10mg / L, N,N-dimethyl dithiocarboxamide propane sulfonate sodium 0.35mg / L, titanium roller grinding offline grinding wheel uses 400 mesh and 600 mesh for one week, and online polishing brush roller uses 1200 mesh. Under this condition, the elongation of lithium battery copper foil produced is as high as 18%, and the appearance, roughness and tensile strength of the lithium battery copper foil are stable.
[0094] The above are merely embodiments of the present application and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. An electrolyte for electrolytic copper foil, characterized in that: The electrolyte for electrolytic copper foil comprises copper ions, sulfate ions, chloride ions, collagen peptides, polyethylene glycol, hydroxyethyl cellulose, sodium polydisulfide propane sulfonate, and 0.25-0.55 mg / L of sodium N,N-dimethyldithiocarboxamide propane sulfonate.
2. The electrolyte for electrolytic copper foil according to claim 1, characterized in that: In the electrolyte for electrolytic copper foil, the concentration of the collagen peptide is 12-20 mg / L, the concentration of the polyethylene glycol is 1-3 mg / L, the concentration of the hydroxyethyl cellulose is 0.1-0.18 mg / L, and the concentration of the sodium polydisulfide dipropane sulfonate is 6-10 mg / L.
3. The electrolyte for electrolytic copper foil according to claim 2, characterized in that: The molecular weight of the collagen peptide is 1500-6000, and the molecular weight of the polyethylene glycol is 4000-6000.
4. The electrolyte for electrolytic copper foil according to claim 1, characterized in that: The electrolyte for electrolytic copper foil comprises copper ions with a concentration of 80-95 g / L and sulfate ions with a concentration of 90-100 g / L.
5. The electrolyte for electrolytic copper foil according to claim 3, characterized in that: The concentration of the chloride ions is 15-30 ppm.
6. A method for preparing copper foil using the electrolytic solution for electrolytic copper foil according to any one of claims 1 to 5, characterized in that: include: injecting the electrolytic copper foil electrolyte into an electrolytic cell; The electrolytic copper foil is electrolytically treated with an electrolyte by a foil machine to obtain copper foil; wherein the anode of the foil machine is a titanium coating, the cathode is a seamless drum-type titanium roller, and the current density of the electrolytic treatment is 50-65A / dm 2 .
7. The method for preparing copper foil using an electrolyte for electrolytic copper foil according to claim 6, characterized in that: The roughness of the roller surface of the seamless drum-type titanium roller is not greater than 0.25 μm.
8. The method for preparing copper foil using an electrolyte for electrolytic copper foil according to claim 7, characterized in that: The step of electrolyzing the electrolytic copper foil with an electrolyte using a foil machine to obtain the copper foil comprises: The seamless drum-type titanium roller was ground offline using a 400-800 mesh grinding wheel.
9. The method for preparing copper foil using an electrolyte for electrolytic copper foil according to claim 8, characterized in that: After the step of offline grinding the seamless drum-type titanium roller using a 400-800 mesh grinding wheel, the method further comprises: The seamless drum-type titanium roller is polished online using a non-woven grinding brush wheel with a mesh size of 1000-1200.
10. A copper foil, characterized in that: The copper foil is prepared by the method for preparing copper foil using an electrolyte for electrolytic copper foil as described in any one of claims 7 to 9.
Citation Information
Cited By
Preparation method of 3-micron ultrathin lithium battery copper foil
CN121295275A